The The Relationship between Digital Leadership of School Administrators and Motivation in the Performance of Teachers under The Secondary Educational Service Area Office Samut Prakan - Chinouan, Wongsakorn; Piatanom, Patumphorn (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
The objectives of this research were to: 1) investigate the level of digital leadership of school administrators; 2) investigate the level of the motivation in the performance of teachers; and 3) examine the relationship between digital Leadership of school administrators and the motivation in the performance of teachers under the Secondary Educational Service Area Office Samut Prakan. The population of research consisted of 333 teachers under the Secondary Educational Service Area Office Samut Prakan in the academic year 2024, which were selected by multi-stage random sampling. The research instrument was a questionnaire with a reliability of 0.987. The data were analyzed by mean standard deviation and Pearson’s Product Moment Correlation Coefficient. The research findings were as follows: 1) The overall digital leadership of school administrators were at a high level 2) The overall of motivation in the performance of teachers were at a high level 3) The relationship between digital Leadership of school administrators and the motivation in the performance of teachers under the Secondary Educational Service Area Office Samut Prakan were positively collected at the high level with the significance level of .01